1983
DOI: 10.1016/0014-5793(83)80033-7
|View full text |Cite
|
Sign up to set email alerts
|

Galanin — a novel biologically active peptide from porcine intestine

Abstract: The isolation of a novel biologically active peptide, designated galanin, is described. The peptide was discovered by the detection of its C‐terminal amide structure in porcine intestinal extract using a chemical method. It was found that galanin consists of 29 amino acids and the complete amino acid sequence is: contract smooth muscle preparations from the rat and to cause a mild and sustained hyperglycemia in dog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
554
1
5

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,455 publications
(570 citation statements)
references
References 19 publications
10
554
1
5
Order By: Relevance
“…In this context, the neuropeptide galanin (Tatemoto et al, 1983) is of particular interest, since it coexists with NA in the locus coeruleus (LC) and with 5-HT in the dorsal raphe (DR) nucleus (Melander et al, 1986;Xu and Hökfelt, 1997;Xu et al, 1998b). Electrophysiological, behavioral, and neurochemical studies have shown that galanin exerts modulatory (mainly inhibitory) effects on both the noradrenergic and serotonergic systems (Seutin et al, 1989;Sevcik et al, 1993;Pieribone et al, 1995;Xu et al, 1998c;Razani et al, 2001;Kehr et al, 2002;see Ö gren et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the neuropeptide galanin (Tatemoto et al, 1983) is of particular interest, since it coexists with NA in the locus coeruleus (LC) and with 5-HT in the dorsal raphe (DR) nucleus (Melander et al, 1986;Xu and Hökfelt, 1997;Xu et al, 1998b). Electrophysiological, behavioral, and neurochemical studies have shown that galanin exerts modulatory (mainly inhibitory) effects on both the noradrenergic and serotonergic systems (Seutin et al, 1989;Sevcik et al, 1993;Pieribone et al, 1995;Xu et al, 1998c;Razani et al, 2001;Kehr et al, 2002;see Ö gren et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, acute injection of galanin or active fragments such as galanin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), into the PVN, lateral and ventromedial hypothalamic nuclei, and the central nucleus of the amygdala, significantly increases food intake and produces rapid increases in the feeding response and total caloric intake [4,5,11,12] . The effects of galanin on feeding be-…”
Section: Effects Of Galanin On Food Intake and Energy Expenditurementioning
confidence: 99%
“…Numerous studies have revealed that the activation of neurons containing galanin in the paraventricular nucleus (PVN) of the hypothalamus augment food intake and body weight [4,5] . Galanin, a 29-amino-acid neuropeptide, is mainly distributed in central and peripheral nervous systems [6] . Currently, it is known that the galanin receptor subtypes include GalR1, GalR2 and GalR3, all of which are G protein-coupled receptors [7] and are distributed in the hypothalamus, amygdala, hippocampus, thalamus, brainstem, spinal cord and dorsal root ganglia [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Galanin is a 29 amino acid neuropeptide (Tatemoto, K., Rokaeus, A., et al 1983) which is widely distributed throughout the peripheral and central nervous system, and is involved in a broad range of brain functions such as food intake (Kalra, S.P. and Horvath, T.L.…”
Section: Introductionmentioning
confidence: 99%